Pengaruh Program Orientasi Terhadap Tingkat Kecemasan dan Tingkat Kepatuhan Pasien Baru di Ruang Bedah Rumah Sakit X Palangka Raya - Erika Sihombing (Syntax Idea)
New patients to the hospital face anxiety due to changes in environment, illness, financing, health workers, loss of privacy and sense of security. Non-compliance with hospital rules and hospital programs. Anxiety and non-compliance can aggravate major health problems, resulting in changes in physical function, quality of life, medication adherence, poor use of healthcareresources. New patient orientation will adapt the patient to the hospital situation and environment. This study aims to obtain an overview of the effect of the orientation program on the level of anxiety and compliance of new patients in the X Hospital Surgery Room, using the quasi experiment pre-test- post-test method with control group design on 56 respondents divided into control and intervention. Quasi experiment pre-test- post-test method with control group design on 56 respondents divided into control group and intervention group.The study found a decrease in anxiety and an increase in new patient compliance and there was an effect of providing an orientation module for reducing anxiety and increasing new patient compliance in the patient group.The new patient orientation module has a positive effect on reducing new patient anxiety and increasing patient compliance during treatment. The results of this study have implications for nursing services that the orientation program can increase compliance and reduce the anxiety of newly admitted patients. The recommendation of this study is that health care facilities must have a good and structured orientation program to improve the adaptation of new patients to the treatment room environment.